ANALISIS TRANSPARANSI DAN AKUNTABILITAS DALAM LAPORAN KEUANGAN DANA DESA PADA DESA GUNUNGTEGUH, SANGKAPURA, BAWEAN - Faizatul Wardah; Miftahol Horri (Jurnal Ilmiah Akuntansi, 2025)
This study aims to analyze the implementation of transparency and accountability principles in the village fund financial statements of GunungTeguh Village, Sangkapura, Bawean in 2023, and to identify influencing factors. The method used is descriptive qualitative with interviews to the Village Head, Financial Officer/Treasurer, and BPD Chairperson, complemented by observation and document study (APBDes, LPPD, Siskeudes). The analysis refers to the indicators of PMK No. 108 of 2024 and Permendagri No. 73 of 2022. The results show that transparency is considered fairly good through physical publication and village meetings, but digital access and information request procedures are not yet optimal. Accountability has been implemented in accordance with regulations, output achievement is 100%, and the outcome provides direct benefits, although it has not been measured quantitatively. Supervision mechanisms by BPD are in place, but there are no formal public complaint procedures and written sanctions. In conclusion, most indicators are met, but improvements are needed in information digitalization, impact evaluation, and participatory supervision strengthening.